题意
默认(nleqslant m)
所求即为:(prodlimits_{i=1}^nprodlimits_{j=1}^mf[gcd(i,j)])
枚举(gcd(i,j))变为:
(prodlimits_{k=1}^{n}f(k)^{sumlimits_{i=1}^nsumlimits_{j=1}^m[gcd(i,j)=k]})
上面那个是莫比乌斯反演套路形式:
(sumlimits_{i=1}^nsumlimits_{j=1}^m[gcd(i,j)=k])
(sumlimits_{i=1}^{frac{n}{k}}sumlimits_{j=1}^{frac{m}{k}}[gcd(i,j)=1])
(sumlimits_{i=1}^{frac{n}{k}}sumlimits_{j=1}^{frac{m}{k}}sumlimits_{x|gcd(i,j)}mu(x))
(sumlimits_{x=1}^{frac{n}{k}}mu(x)sumlimits_{i=1}^{frac{n}{k}}sumlimits_{j=1}^{frac{m}{k}}[x|gcd(i,j)])
(sumlimits_{x=1}^{frac{n}{k}}mu(x)sumlimits_{i=1}^{frac{n}{k*x}}sumlimits_{j=1}^{frac{m}{k*x}}1)
(sumlimits_{x=1}^{frac{n}{k}}mu(x)frac{n}{k*x}frac{m}{k*x})
代回原式:
(prodlimits_{k=1}^{n}f(k)^{sumlimits_{x=1}^{frac{n}{k}}mu(x)frac{n}{k*x}frac{m}{k*x}})
设(T=k*x),转而枚举(T):
(prodlimits_{T=1}^{n}prodlimits_{d|T}f(d)^{mu(frac{T}{d})frac{n}{T}frac{m}{T}})
(prodlimits_{T=1}^{n}(prodlimits_{d|T}f(d)^{mu(frac{T}{d})})^{frac{n}{T}frac{m}{T}})
显然指数部分可以除法分块,考虑如何求(prodlimits_{d|T}f(d)^{mu(frac{T}{d})}):
设(g(T)=prodlimits_{d|T}f(d)^{mu(frac{T}{d})})
在算到(f(d))时乘到(g(T))即可。
答案即为:
(prodlimits_{T=1}^{n}g(T)^{frac{n}{T}frac{m}{T}})
code:
#include<bits/stdc++.h>
using namespace std;
typedef long long ll;
const int maxn=1e6+10;
const ll mod=1e9+7;
int T,n,m;
ll ans=1;
ll f[maxn],g[maxn],mu[maxn],invf[maxn];
bool vis[maxn];
vector<int>prime;
inline ll power(ll x,ll k,ll mod)
{
ll res=1;
while(k)
{
if(k&1)res=res*x%mod;
x=x*x%mod;k>>=1;
}
return res;
}
inline void pre_work(int n)
{
g[0]=g[1]=1;
vis[1]=1;mu[1]=1;
for(int i=2;i<=n;i++)
{
g[i]=1;
if(!vis[i])prime.push_back(i),mu[i]=-1;
for(unsigned int j=0;j<prime.size()&&i*prime[j]<=n;j++)
{
vis[i*prime[j]]=1;
if(i%prime[j]==0)break;
mu[i*prime[j]]=-mu[i];
}
}
f[0]=0,f[1]=1;invf[1]=1;
for(int i=2;i<=n;i++)f[i]=(f[i-1]+f[i-2])%mod,invf[i]=power(f[i],mod-2,mod);
for(int i=1;i<=n;i++)
{
if(!mu[i])continue;
for(int j=i;j<=n;j+=i)
g[j]=g[j]*(mu[i]==1?f[j/i]:invf[j/i])%mod;
}
for(int i=2;i<=n;i++)g[i]=g[i]*g[i-1]%mod;
}
int main()
{
pre_work(1000000);
scanf("%d",&T);
while(T--)
{
ans=1;
scanf("%d%d",&n,&m);
if(n>m)swap(n,m);
for(int l=1,r;l<=n;l=r+1)
{
r=min(n/(n/l),m/(m/l));
ans=ans*power(g[r]*power(g[l-1],mod-2,mod)%mod,1ll*(n/l)*(m/l)%(mod-1),mod)%mod;
}
printf("%lld
",(ans+mod)%mod);
}
return 0;
}